The Effect of Storytelling Marketing on Purchase Intention Through Brand Experience and Brand Engagement - Mahjudin Mahjudin; Dody Suhermawan (PT. Mawadaku Sukses Solusindo, 2026)
The cosmetics industry has experienced substantial growth over the past decade, accompanied by significant changes in consumer behavior, particularly among Generation Z consumers who increasingly value emotional connections, brand narratives, and meaningful experiences when making purchasing decisions. In response to these changes, storytelling marketing has emerged as an important strategy for creating emotional bonds between brands and consumers. However, previous studies have predominantly examined the influence of storytelling marketing on purchase intention through either brand experience or brand engagement separately, resulting in limited understanding of their simultaneous mediating roles. Therefore, this study aims to analyze the effect of storytelling marketing on purchase intention through brand experience and brand engagement among Premium make up brandmakeup makeup consumers in Surabaya. This study employed a quantitative explanatory approach using a survey method. Data were collected through online questionnaires distributed to university students in Surabaya who had purchased premium make up brandmakeupproducts and were familiar with storytelling marketing content on social media. A purposive sampling technique was applied, resulting in 250 respondents. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The analysis included assessments of the measurement model and structural model, as well as hypothesis testing and mediation analysis through bootstrapping procedures. The findings indicate that storytelling marketing does not have a significant direct effect on purchase intention. However, storytelling marketing has a positive and significant effect on both brand experience and brand engagement. Furthermore, brand experience and brand engagement significantly influence purchase intention, with brand engagement demonstrating the strongest effect. The mediation analysis reveals that both brand experience and brand engagement significantly mediate the relationship between storytelling marketing and purchase intention. These findings suggest that storytelling marketing is more effective in enhancing consumers’ purchase intentions through the creation of meaningful brand experiences and active consumer engagement rather than through direct influence alone.